Histone Arginine Methyltransferase CARM1-Mediated H3R26me2 Is Essential for Morula-to-Blastocyst Transition in Pigs - Cao, Zubing; Tong, Xu; Yin, Huiqun; Zhou, Naru; Zhang, Xiangdong; Zhang, Mengya; Wang, Xin; Liu, Qiuchen; Yan, Yelian; Ma, Yangyang; Yu, Tong; Li, Yunsheng; et al. (Frontiers in Cell and Developmental Biology, 2021)
Coactivator-associated arginine methyltransferase 1 (CARM1) is involved in both establishment of first pluripotent lineage and pluripotency maintenance of embryonic stem cells (ESCs) in mice. However, the histone substrates and role of CARM1 in early embryonic development remain largely unknown. Here, we show that CARM1 specifically catalyzes H3R26me2 to promote porcine blastocyst formation. The putative histone substrates of CARM1, including H3R2me2, H3R17me2, and H3R26me2, are present in pig early embryos. The changes of CARM1 mRNA during early embryogenesis parallel that of H3R26me2. Functional studies using a combinational approach of chemical inhibition and RNA interference (RNAi) showed that catalytic activity inhibition of CARM1 protein or knockdown (KD) of CARM1 mRNA did not alter the levels of both H3R2me2 and H3R17me2, but significantly reduced H3R26me2 levels in porcine embryos. Furthermore, CARM1 inhibition or KD did not affect embryo development to the 2-cell, 4-cell, 8-cell, and morula stages, but severely compromised blastocyst development. CARM1 knocked down embryos that developed to the blastocyst stage had fewer total cells, inner cell mass (ICM), and trophectoderm (TE) cells. Mechanistically, single embryo RNA-sequencing analysis revealed that CARM1 KD altered the transcriptome characterized by downregulation of key genes associated with Hippo and PI3K-AKT signaling pathways. Taken together, these results demonstrate that CARM1 specifically catalyzes H3R26me2 in porcine embryos and participates in blastocyst development.